1982
DOI: 10.3171/jns.1982.56.2.0241
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal and intraventricular morphine for pain in cancer patients: initial study

Abstract: Intractable pain in six cancer patients was treated with lumbar intrathecal morphine (two patients) and intraventricular morphine (four patients). Daily percutaneous injections of morphine through Ommaya reservoirs were made. Initially, 1 mg of lumbar intrathecal morphine resulted in pain relief for 10 to 14 hours, and 2.5 to 4.0 mg of intraventricular morphine gave relief for 12 to 24 hours. This treatment was continued for 3 to 7 months in three of the adults. Morphine requirements gradually increased. Side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
22

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(45 citation statements)
references
References 10 publications
0
23
0
22
Order By: Relevance
“…Paradoxically, the risks of central respiratory depression are rela tively high after intraventricular administration of low doses of mor phine [6,7,12,14] and can be immediately reversed by naloxone. But all these patients have already received morphine systematically and as a result must have reduced sensitivity of opiate receptors [5,6,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, the risks of central respiratory depression are rela tively high after intraventricular administration of low doses of mor phine [6,7,12,14] and can be immediately reversed by naloxone. But all these patients have already received morphine systematically and as a result must have reduced sensitivity of opiate receptors [5,6,12].…”
Section: Discussionmentioning
confidence: 99%
“…But all these patients have already received morphine systematically and as a result must have reduced sensitivity of opiate receptors [5,6,12]. Mi nor and transient side effects, like nausea, vomiting, skin reactions and itching, occurred with the same rate in both [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Since Wang reported the administration of intrathecal morphine for pain relief in 1979, 24 There have been several applications of this technique for relief of both chronic, 25 and acute pain, 26,27,28 as well as for pain associated with labour. 29,30,31 Intrathecal morphine has been employed for postoperative analgesia in a wide range of doses, from 0.5 mg in patients after inguinal herniorrhapliy, 32 to 20 mg after laparotomy or thoracotomy 33 .…”
Section: Duration Of Analgesiamentioning
confidence: 99%
“…The human application was promoted by the fact that direct IT morphine offered greater control of drug levels and rapid reversibility, produced fewer side effects, and offered superior pain control for certain refractory pain types. 4 In the early 1980s, Rico et al 5 and Leavens et al 6 both reported satisfactory analgesic effects with minimal side effects in patients treated with boluses of IT morphine. Both groups reported moderate to significant pain relief in a majority of the cancer patients studied (Rico et al, 78%; Leavens et al, and 66%), using individual IT injections of morphine.…”
Section: Intrathecal Pain Managementmentioning
confidence: 99%